Case Studies in Information and Computer Ethics - Spinello Richard A (Prentice Hall, 1997)
This book offers a collection of diverse cases to help students and computer professionals reflect upon the complex and multi-faceted ethical dilemmas that are emerging in the information age. Preface, Introduction, Computers and Information, Frameworks for Ethical Analysis, Information Ethics, The Acquisition of Information, Information Access, Information Stewardship, Computer Science Ethics, Software Ownership and Intellectual Property Issues, Computer Security and Computer Crimes, Liability and Safety and Reliability, Social Issues, The Social Impact of Computer Technology, References, Appendix, Index.